2019
DOI: 10.3389/fimmu.2019.02173
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Inhalation Attenuated the Effects of Budesonide on Aspergillus fumigatus-Induced Airway Inflammation and Hyperreactivity in Mice

Abstract: Inhaled glucocorticoids form the mainstay of asthma treatment because of their anti-inflammatory effects in the lung. Exposure to the air pollutant ozone (O3) exacerbates chronic airways disease. We and others showed that presence of the epithelial-derived surfactant protein-D (SP-D) is important in immunoprotection against inflammatory changes including those induced by O3 inhalation in the airways. SP-D synthesis requires glucocorticoids. We hypothesized here that O3 exposure impairs glucocorticoid responsiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 75 publications
(123 reference statements)
1
19
0
Order By: Relevance
“…Patients with severe asthma and COPD often exhibit greater levels of oxidative stress biomarkers, with increased levels correlating with worsened symptoms, decreased lung function, and corticosteroid insensitivity [37,75,[78][79][80][81][82][83]. This oxidative burden is achieved by exposure to environmental and cellular sources of RONS.…”
Section: Factors Contributing To Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with severe asthma and COPD often exhibit greater levels of oxidative stress biomarkers, with increased levels correlating with worsened symptoms, decreased lung function, and corticosteroid insensitivity [37,75,[78][79][80][81][82][83]. This oxidative burden is achieved by exposure to environmental and cellular sources of RONS.…”
Section: Factors Contributing To Oxidative Stressmentioning
confidence: 99%
“…Increases in pollutant levels contribute to disease pathogenesis and exacerbations in asthma and COPD [80,81,102]. Ozone is an oxidant that induces Th17-mediated neutrophilic airway inflammation and is associated with decreased corticosteroid sensitivity [79,103,104]. Exposure to other environmental pollutants, such as diesel exhaust and <2.5 µm particulate matter (PM 2.5 ), also induces high levels of oxidative stress in the lung [82,83,105].…”
Section: Environmental Sourcesmentioning
confidence: 99%
“…O 3 exposure results in accumulation of reactive oxygen species (ROS) most likely through lipid peroxidation processes of the pulmonary surfactant phospholipids (60) and cell membranes (126)(127)(128). ROS in turn rapidly activate the release of alarmins IL-1b, IL-6, IL-23, IL-33, TNF-a, and TSLP (Figure 1A) leading to a cascade of proinflammatory changes in structural and immune cells in the respiratory mucosal tissue (106,116,122,129,(131)(132)(133)(134)(135)(136). Activation of the RORgt proinflammatory signaling pathway leads to mRNA transcription of the IL-17A and IL-22 genes (Figure 1B) (131,(137)(138)(139)(140)(141)(142)(143)(144)(145)(146).…”
Section: O 3 -Induced Airway Inflammation and Glucocorticoid Resistancementioning
confidence: 99%
“…Because asthmatic patients respond to O 3 with an enhanced airway neutrophilic influx compared with non-asthmatic controls (155), the observation that neutrophils are poorly responsive to glucocorticoids ( 15) raises a serious concern related to asthma treatment. Indeed, recent studies demonstrated that O 3 impaired the effects of glucocorticoid treatment in a mouse model of allergen-induced asthma in vivo as well as in human cell lines and primary epithelial cells in vitro (58,122,156). What are the underlying molecular mechanisms of O 3 -induced glucocorticoid resistant neutrophilic airway inflammation in asthma?…”
Section: O 3 -Induced Airway Inflammation and Glucocorticoid Resistancementioning
confidence: 99%
See 1 more Smart Citation